(untitled) (Journal of Atomic and Molecular Sciences, 2012)
We propose gold slit arrays with Y-shaped channels and investigate their transmission properties numacially. Results indicate that the surface plasmon resonance peak value keeps unchanged and the localized waveguide resonance peak red-shifts and falls obviously when the entrance slit width narrows. However when the entrance slit becomes extremely small the surface plasmon resonance peak red-shifts and falls sharply. Furthermore as the slit length increases, firstly the surface plasmon resonance peak splits into two peaks, the right peak value rise and they slowly converged into one single peak. To understand its physical origin, surface plasmon resonance and Fabry-Perot cavity resonance theories are suggested. We simulate their electric field distributions and find the electric fields become stronger as the slit become narrower or the dielectric constant become smaller. The results may be useful for the design of frequency-selective sensor and optical devices in the future.